A closer look at the morphological and molecular diversity of Neoechinorhynchus (Acanthocephala) in Middle American cichlids (Osteichthyes: Cichlidae), with the description of a new species from Costa Rica. (2020) - Pinacho-Pinacho, C.D.; Sereno-Uribe, A.L.; García-Varela, M.; Pérez-Ponce de León, G.
Abstract: Neoechinorhynchus is one of the most speciose genera of acanthocephalans, with approximately 116 described species. A recent study, aimed at establishing the genetic diversity of Neoechinorhynchus in Middle American freshwater fishes, validated nine species molecularly and morphologically and revealed the existence of 10 putative candidate species. Neoechinorhynchus golvani, a parasite commonly found in cichlids throughout Middle America with an allegedly large intraspecific morphological variability, was found to represent a species complex; species delimitation methods uncovered three additional genetic lineages. Here, we re-analyse the morphological and molecular data for N. golvani species complex infecting cichlids in that geographical area. A multivariate analysis of variance (MANOVA) was conducted particularly for the length of apical, middle and posterior hooks of the species/lineages of Neoechinorhynchus in cichlids, revealing morphological variation in the length of apical hooks for Lineage 8, although no morphological distinction was observed for Lineages 9 and 10. A new concatenated phylogenetic analysis of one mitochondrial and two ribosomal DNA genes was used to further corroborate the species delimitation among lineages; Neoechinorhynchus Lineage 8 was found to be morphologically and genetically distinct from its sister taxa, N. golvani and other two undescribed genetic lineages, and is formally described as a new species. Neoechinorhynchus costarricense n. sp. is described from the intestines of eight species of cichlids in Costa Rica. The new species is distinguished from the other species/lineages of Neoechinorhynchus in cichlids mainly by the size of the apical hooks of the proboscis.